Changes of indicators of high-speed and high-speed and power preparedness at volleyball players of 12-13 years old - Oleg Shevchenko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to define changes of indicators of high-speed and high-speed and power preparedness of volleyball players of 12-13 years old. Material & Methods: the test exercises, which are recommended by the training program of CYSS on volleyball, were used for the definition of the level of development of high-speed and high-speed and power abilities of volleyball players. 25 young volleyball players from the group of the previous basic preparation took part in the experiment. Sports experience of sportsmen is 3-4 years. The analysis of scientifically-methodical literature, pedagogical testing, pedagogical experiment, methods of mathematical statistics were carried out. Results: the analyzed level of high-speed and high-speed and power abilities of volleyball players. Conclusions: the results had reliable changes (t=2,2-2,4 at р<0,05) of the level of high-speed and high-speed and power abilities of volleyball players of 12-13years old in the experimental group at the end of the experiment, except run on 30 m that demonstrates a positive influence of application of special exercises in the educational-training process.